2013
DOI: 10.5755/j01.ms.19.1.3834
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Moisture Absorption Properties during the Service Life of External Thermal Insulation Composite System

Abstract: This paper provides initial results from experimental work on the durability of external thermal insulation composite system (ETICS). In order to predict service life of ETICS, the accelerated climatic cycle was composed on the basis of earlier scientific research and the statistic data of the Lithuanian climate. The research aims to assess the durability and service life of finishing coat by calculating the amount of moisture while measuring the 24 h water absorption of the samples during water absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…One of the primary promoters of the degradation of external claddings is exposure to damp [52]. The presence of moisture in conjunction with salts significantly increases the degradation rate of external claddings, leading to aesthetic anomalies (such as scaling, flaking, efflorescence, strains, and biological growth) or more severe anomalies (such as cracking, swelling, detachment, spilling, and material loosening) [53][54][55][56]. In this study, exposure to damp is divided into two categories: (i) Low, for claddings in buildings located in an urban context, at more than 5 km from the sea and without the influence of dominant winds carrying sea salts; and (ii) high, for buildings located closer to the sea or other humidity sources, under the direct influence of sea winds, or in areas with an average annual rainfall higher than 500 mm or average annual relative humidity higher than 75%.…”
Section: Exposure To Dampmentioning
confidence: 99%
“…One of the primary promoters of the degradation of external claddings is exposure to damp [52]. The presence of moisture in conjunction with salts significantly increases the degradation rate of external claddings, leading to aesthetic anomalies (such as scaling, flaking, efflorescence, strains, and biological growth) or more severe anomalies (such as cracking, swelling, detachment, spilling, and material loosening) [53][54][55][56]. In this study, exposure to damp is divided into two categories: (i) Low, for claddings in buildings located in an urban context, at more than 5 km from the sea and without the influence of dominant winds carrying sea salts; and (ii) high, for buildings located closer to the sea or other humidity sources, under the direct influence of sea winds, or in areas with an average annual rainfall higher than 500 mm or average annual relative humidity higher than 75%.…”
Section: Exposure To Dampmentioning
confidence: 99%
“…The results obtained by the average degradation curve seem more reliable since they reveal that the darker colours tend to present a lower estimated service life. Various authors (Daniotti & Paolini, 2008;Norvaišienė, Griciutė, Bliūdžius, & Ramanauskas, 2013;Fernandes et al, 2016b) refer that ETICS with dark colours tend to present a faster deterioration rate, especially in warm climates, when exposed for several hours to UV radiation, due to the higher thermal gradient effect. However, in some situations it is not possible to achieve conclusive results for a given characteristic of the ETICS, when analysed separately, since the degradation of ETICS is influenced by several factors and the presence of anomalies is generally caused by the combined action of various degradation agents, which may occur simultaneously, and whose synergy can change the normal pathology of the cladding systems after a long period of time (Amaro et al, 2013;Sulakatko, Lill, & Liisma, 2015).…”
Section: Factor a -Materials Characteristicsmentioning
confidence: 99%
“…However, is it necessary to use all these test methods, moreover the earlier studies showed, that the most simple and reliable indicator of render's ageing is the change of water absorption rate during the ageing. (ASHREA 2010, Topcu and Merkel 2008, Norvaišienė et al 2011, Koči et al 2012 By summarizing all above mentioned accelerated ageing methods, one matter arises: why such climate impacts, durations and amplitudes are chosen for determination of ETICS durability?…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, accelerated ageing ought to be as similar as natural ageing. Several experiments were performed concerning ETICS service life and different results were obtained due to different test methods (Shohet and Paciuk 2004, Daniotti and Paolini 2005, Bochen et al 2005, Jelle et al 2008, Bochen 2009, Bochen and Gil 2009, Koči et al 2012, Norvaišienė et al 2011.…”
Section: Introductionmentioning
confidence: 99%